การสังเคราะห์อนุภาคนาโนทองแดงสำหรับตรวจวัดโปรตีนในอาหาร - พศวีร์ พรพินิจสุวรรณ (จุฬาลงกรณ์มหาวิทยาลัย, 2016)
Copper nanoparticles were synthesized by reduction method, using copper(II) sulfate, tri-sodium citrate and hydrazine for copper precursor, stabilizer and reducing agent, respectively, in molar ratio of 1:8:6. Copper nanoparticles were characterized using X-ray Diffraction (XRD), Transmission Electron Microscope (TEM) and UV-vis Spectroscopy, and it was found that copper nanoparticles have diameter of around 30 nm. Copper nanoparticles were then used for determining protein content of standard solution (Bovine Serum Albumin; BSA) and sample solution (milk) by UV-vis Spectroscopy. Protein content was detected in a linear range of 0-16 μg/mL for both solutions. The limit of detection is 3 x 10⁻⁵ mg/mL for BSA solution and 8 x 10⁻⁵ mg/mL for milk solution. The effect of concentration of copper nanoparticles on protein content measurement was studied. The more copper nanoparticles, the wider linear range for protein content measurement.